The supernova that destroyed a protogalaxy: prompt chemical enrichment and supermassive black hole growth - Whalen, Daniel J.; Johnson, Jarrett L.; Smidt, Joseph; Meiksin, Avery; Heger, Alexander; Even, Wesley; Fryer, Chris L. (The astrophysical journal, 2013)
The first primitive galaxies formed from accretion and mergers by z ∼ 15, and were primarily responsible for cosmological reionization and the chemical enrichment of the early cosmos. But a few of these galaxies may have formed in the presence of strong Lyman-Werner UV fluxes that sterilized them of H2, preventing them from forming stars or expelling heavy elements into the intergalactic medium prior to assembly. At masses of 108 M☉ and virial temperatures of 104 K, these halos began to rapidly cool by atomic lines, perhaps forming 104-106 M☉ Pop III stars and, later, the seeds of supermassive black holes. We have modeled the explosion of a supermassive Pop III star in the dense core of a line-cooled protogalaxy with the ZEUS-MP code. We find that the supernova (SN) expands to a radius of ∼1 kpc, briefly engulfing the entire galaxy, but then collapses back into the potential well of the dark matter. Fallback fully mixes the interior of the protogalaxy with metals, igniting a violent starburst and fueling the rapid growth of a massive black hole at its center. The starburst would populate the protogalaxy with stars in greater numbers and at higher metallicities than in more slowly evolving, nearby halos. The SN remnant becomes a strong synchrotron source that can be observed with eVLA and eMERLIN and has a unique signature that easily distinguishes it from less energetic SN remnants. Such explosions, and their attendant starbursts, may well have marked the birthplaces of supermassive black holes on the sky.
Gesehen am 04.11.2021